Government Service Insurance System loans administration department - Carreon, John Philip Q.; Dicdican, Ruth Y.; Leyva, Ruby Gisela G.; Saquing, Flordeliz D. (Diliman, Quezon City College of Engineering, 1991)
The systems and procedures study made on the Loans Administration Department 1 can be divided into three main parts. The first part is the formulation of the problem. The second part is the analysis of the present system. And the last part is the generation and evaluation of alternative solutions to the problem. In doing this, the background of the site is also considered. The main report consists of eight chapters. The first chapter states the objectives of the study set by the authors. The second chapter contains the background on the Government Service Insurance System since the department covered by the study is located in this structure. The scope and problem of the study is found in the third chapter. While the fourth chapter contains the description of the work hierarchy, objectives, functions, divisions, present process and working conditions of the subject under study-the Loans Administration Department 1. The fifth chapter is the analysis of the present system in terms of the workflow, layout, equipment used, forms used and working conditions. Generation of alternatives is found in the sixth chapter while the evaluation of such alternatives is in the seventh chapter. The eighth chapter contains the specification of the solutions arrived at by the authors of the study. There are charts, diagrams and photographs included in the report to aid the reader's understanding of the study.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 32 : Methods Engineering
Keywords: Systems analysis